Limits of validity for a semiclassical mean-field two-fluid model for Bose-Einstein condensation thermodynamics - Adhikari, S. K.; Gammal, A. (Elsevier B.V., 2000)
We reinvestigate the Bose-Einstein condensation (BEC) thermodynamics of a weakly interacting dilute Bose gas under the action of a trap using a semi-classical two-fluid mean-field model in order to find the domain of applicability of the model. Such a model is expected to break down once the condition of diluteness and weak interaction is violated. We find that this breakdown happens for values of coupling and density near the present experimental scenario of BEG. With the increase of the interaction coupling and density the model may lead to unphysical results for thermodynamic observables. (C) 2000 Published by Elsevier B.V. B.V, All rights reserved.
Keywords: Bose-Einstein condensation; thermodynamical observables